Uncertainties in the adaptation of alpine pastures to climate change based on remote sensing products and modelling. (15th June 2023) - Brilli, L.; Martin, R.; Argenti, G.; Bassignana, M.; Bindi, M.; Bonet, R.; Choler, P.; Cremonese, E.; Della Vedova, M.; Dibari, C.; Filippa, G.; Galvagno, M.; et al.
Abstract: Over the last century, the management of pastoral systems has undergone major changes to meet the livelihood needs of alpine communities. Faced with the changes induced by recent global warming, the ecological status of many pastoral systems has seriously deteriorated in the western alpine region. We assessed changes in pasture dynamics by integrating information from remote-sensing products and two process-based models, i.e. the grassland-specific, biogeochemical growth model PaSim and the generic crop-growth model DayCent. Meteorological observations and satellite-derived Normalised Difference Vegetation Index (NDVI) trajectories of three pasture macro-types (high, medium and low productivity classes) in two study areas - Parc National des Écrins (PNE) in France and Parco Nazionale Gran Paradiso (PNGP) in Italy - were used as a basis for the model calibration work. The performance of the models was satisfactory in reproducing pasture production dynamics (R 2 = 0.52 to 0.83). Projected changes in alpine pastures due to climate-change impacts and adaptation strategies indicate that: i) the length of the growing season is expected to increase between 15 and 40 days, resulting in changes in the timing and amount of biomass production, ii) summer water stress could limit pasture productivity; iii) earlier onset of grazing could enhance pasture productivity; iv) higher livestock densities could increase the rate of biomass regrowth, but major uncertainties in modelling processes need to be considered; and v) the carbon sequestration potential of pastures could decrease under limited water availability and warming. Graphical abstract: Image 1 Highlights: Alpine pastures are vulnerable to climate change. Remote sensing and modelling support vulnerability analysis in the western Alps. Earlier grazing, not changes in cattle density, copes with increased vulnerability. Summer water stresses and warming may lower C sequestration by pastures.